Crayfish pet trade as a pathway for the introduction of known and novel viruses - Bačnik, Katarina; Kranjc, Luka; Botella, Leticia; Maguire, Ivana; Pavić, Dora; Patoka, Jiří; Dragičević, Paula; Bláha, Martin; Bielen, Ana; Kouba, Antonín; Kutnjak, Denis; Hudina, Sandra (Journal of invertebrate pathology, 2025)
Expanding international pet trade has emerged as one of the main introduction pathways of aquatic invasive species, with ornamental crayfish species commonly available on the EU and global markets. Besides most frequently studied crayfish pathogens, such as Aphanomyces astaci and white spot syndrome virus (WSSV), ornamental crayfish carry associated microbial communities, which may potentially lead to the emergence of known or even novel diseases following intentional or unintentional release of animals into the wild. This is especially problematic in the case of viruses, which represent an important, yet considerably understudied, group of crayfish pathogens. Here we analyzed viromes of hepatopancreas tissue of four crayfish species acquired in the international pet trade in Europe (Procambarus clarkii, Procambarus alleni, Cherax holthuisi, and Cherax quadricarinatus) using a high throughput sequencing based metagenomic approach. Seven different known viruses were identified, which were previously either directly associated with crayfish (WSSV, Cherax quadricarinatus reovirus, chequa iflavirus, athtab bunya-like virus) or with hosts from subphylum Crustacea or invertebrates associated with freshwater environment (Shahe ispoda virus 5, Dicistroviridae sp.). Additional sequences represented 8 potential novel and divergent RNA viruses, most similar to sequences belonging to members of Picornavirales, Elliovirales, Reovirales, Hepelivirales, Tolivirales and Ghabrivirales orders. We discuss our findings in relation to their phylogenetic relationships, geographical origins, and putative pathogenicity implications. The results highlight the need for further research into the risks related to disease emergence associated with the pet trade.
Keywords: Ornamental crayfish; severní raci; Virome; zavlečené druhy; Animals; Pets; Astacoidea; High throughput sequencing; virom; Pet-trade; novel RNA viruses; zvířata; Introduced Species; domácí zvířata